2009
DOI: 10.1007/s12237-009-9212-6
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellate Cysts in Coastal Sediments as Indicators of Eutrophication: A Case of Gwangyang Bay, South Sea of Korea

Abstract: Diatom densities in the surface water and dinoflagellate cysts in bottom sediments of Gwangyang Bay were studied to determine changes in the phytoplankton community structure in response to anthropogenic eutrophication and to assess the use of dinoflagellate cysts as indicators of coastal eutrophication. Our results show that, in nutrient-enriched environments, diatoms are particularly benefited from the nutrients supplied and, as a consequence, heterotrophic dinoflagellates that feed on the diatoms can be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
2
13
0
3
Order By: Relevance
“…during summer and winter in Gwangyang Bay (Choi et al, 1998;Baek et al, 2015). Kim et al (2009) also reported that diatom and dinoflagellate communities have experienced a considerable change because of increased nutrient loadings from both domestic sewage and industrial pollution during summer. Therefore, the seasonal change in the phytoplankton species composition and community structure could lead to a determination of the different biochemical pools on a seasonal basis.…”
Section: Environmental Conditions and Biochemical Poolsmentioning
confidence: 99%
“…during summer and winter in Gwangyang Bay (Choi et al, 1998;Baek et al, 2015). Kim et al (2009) also reported that diatom and dinoflagellate communities have experienced a considerable change because of increased nutrient loadings from both domestic sewage and industrial pollution during summer. Therefore, the seasonal change in the phytoplankton species composition and community structure could lead to a determination of the different biochemical pools on a seasonal basis.…”
Section: Environmental Conditions and Biochemical Poolsmentioning
confidence: 99%
“…However, modern foraminiferal distribution is still dominated by the opportunistic species. In addition to foraminiferal and ostracod records, dinoflagellate microfossils are also abundant in Japanese and Korean embayments, and show eutrophication-induced increases in heterotrophic species during the early to mid 20th century (Matsuoka 1995;Kim and Matsuoka 1998;Matsuoka 1999;Matsuoka and Kim 1999;Matsuoka 2001;Kim et al 2009;Matsuoka and Shin 2010;Shin et al 2010).…”
Section: Asian Watersmentioning
confidence: 99%
“…Dinoflagellates have species specific differential environmental and growth requirements, thus their cyst distribution in sediments can portray surface water conditions (Dale, 2001;Marret and Zonneveld, 2003;Zonneveld et al, 2013). Higher abundance of autotrophic species in sediments reveals stable water conditions with increased light penetration and ample nutrient supply in water column, whereas increased abundance of heterotrophic species cysts reveals availability of prey organisms and productivity changes (Zonneveld, 1997a;Marret and Zonneveld, 2003;Kim et al, 2009;Zonneveld et al, 2013). In recent surface sediments, dinoflagellate cyst distribution patterns have shown correlation with regionally varying surface water masses, physico-chemical (temperature, salinity, dissolved oxygen, nutrients) and biological (food availability, productivity) factors (Marret and Zonneveld, 2003;Zonneveld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%